The expectations of primary, high school and university students towards ICT education - Sergo Kuruliszwili (Edukacja Ustawiczna Dorosłych)
Selection of the curriculum content in information technology education is a difficult task, both due to the different range of skill levels in various groups of students and the rapid devaluation of some of the subjects. Curriculums, which usually contain generally defined content, giving the freedom of choice as to how to implement it, are developed by expert teams, not leaving much margin for the needs formulated by students. The paper attempts to discuss the process of creating information technology curricula for primary, secondary and humanities students. In the line of deliberations there is a question whether the opinion of students who articulate their expectations in this respect should be taken into account in the process of creating ICT curricula. This opinion is presented in the results of conducted research,